Popular Music and Human Rights : (Two-volume set). - Peddie, Ian (Ashgate popular and folk music series., 2011)
Popular music has long understood that human rights, if attainable at all, involve a struggle without end. The right to imagine an individual will, the right to some form of self-determination and the right to self-legislation have long been at the forefront of popular music's approach to human rights. At a time of such uncertainty and confusion, with human rights currently being violated all over the world, a new and sustained examination of cultural responses to such issues is warranted. In this respect music, which is always produced in a social context, is an extremely useful medium; in it.